Answer:
2x+12
Step-by-step explanation:
2x+3(x−2)−3(x−6)
Distribute:
=2x+(3)(x)+(3)(−2)+(−3)(x)+(−3)(−6)
=2x+3x+−6+−3x+18
Combine Like Terms:
=2x+3x+−6+−3x+18
=(2x+3x+−3x)+(−6+18)
=2x+12
Answer:
=2x+12
Answer: second option
Step-by-step explanation: To solve this problem, we will need to plug in the value of “x” into our equation to see if it makes sense.
Let’s start by going in order.
-4.9 = -5.7 + 10.6 = 4.9
This will not be the answer because it’s positive 4.9 not negative.
Let’s go on to the last one. If we add positive 0.8 to negative 5.7 we will get the answer of -4.9 and this makes sense.
One pound is 16 oz. just multiply 22 by 16 and boom, there's your answer